Turning math attractive to computer science students: an application-to-model approach - Manacero, Aleardo [UNESP]; Marranghello, Norian [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
This paper describes an innovative approach to develop the understanding about the relevance of mathematics to computer science. The mathematical subjects are introduced through an application-to-model scheme that lead computer science students to a better understanding of why they have to learn math and learn it effectively. Our approach consists of a single one semester course, taught at the first semester of the program, where the students are initially exposed to some typical computer applications. When they recognize the applications' complexity, the instructor gives the mathematical models supporting such applications, even before a formal introduction to the model in a math course. We applied this approach at Unesp (Brazil) and the results include a large reduction in the rate of students that abandon the college and better students in the final years of our program.
Keywords: Computer science; Information dissemination; Mathematical models; Students; Application to model approach; Undergraduate student; Curricula